Censorship detected in UZ (Uzbekistan) - Voidly (2026)
CRITICAL severity censorship detected in Uzbekistan. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: UZ-2026-0325
Keywords: censorship; UZ; censorship; critical